A direção de tratamento e a política na saúde mental pública: articulações psicanalíticas sobre o bem-dizer - Dias, Ana Carolina Afonso Lima (2024)
In this thesis, we articulate the construction of the discharge process and its dissonances in the field of public mental health, organized by questions that touch on the ethical-political dimensions that emerge in this context. Based on the inseparability of clinical and political aspects of the Unified Health System (SUS), we investigated the consequences of this inseparability, highlighting its impact on clinical practice in public mental health. To this end, we start with discussions about the Singular Therapeutic Projects (PTS), problematizing a certain compulsoriness in treatments, culminating in endless treatments, in which the subject and the institution end up solidifying. In order to develop this issue, we present the bases of the discourse of biomedicine in its causal-control reasoning and psychoanalysis based on the logic of the unconscious, analyzing the different logics in question and their repercussions on the direction of treatment, addressing how discharge is ordered in the different fields. We have discussed in detail how the field of mental health has been crossed by the process of the commodification of health, highlighting its effects on the construction of care paths, in view of the harmful impacts that the takeover of mental health by the aegis of capital produces. The proposal coined in this thesis is that the PTS can have a non-total discharge as one of the possible referrals, built on the singularity of each case. In this construction, we followed Lacan's conceptualizations, postulating the not-all logic and its ethical reverberations in the construction of the treatment direction. With the intention of advancing these issues, we made an incursion into classical Aristotelian logic, highlighting its main premises and, in counterpoint, we highlighted the ethics of psychoanalysis from its ordering by the unique and singular saying well. We directed the articulations towards the possible conjunctions of politics in the SUS with the politics of psychoanalysis, based on its orientation via the politics of the lack-of-being, as proposed by Lacan, elevating what is good to say and the construction of a know-how, based on the singular inventions that emerge from psychic work as the organizing axes of clinical work in the SUS. The direction of this study was based on the possibility of making policy, in the context of public mental health, aligned with the politics and ethics of psychoanalysis, in the sense of working against the tutelage and power devices of the state, emphasizing the singular as the basis for the direction of treatment